What clinical trials are needed for treatment of leiomyosarcoma? - Kasper, Bernd; D’Ambrosio, Lorenzo; Davis, Elizabeth J.; Ingham, Matthew; Broto, Javier Martin; Trent, Jonathan C.; van Houdt, Winan J.; Van Tine, Brian A. (Current treatment options in oncology, 2022)
Leiomyosarcoma is one of the most common subtypes of soft tissue sarcomas accounting for approximately 20% of sarcomas. As leiomyosarcoma patients frequently develop metastatic disease, effective systemic therapies are needed to improve clinical outcomes. The overall activity of the currently available conventional systemic therapies and the prognosis of patients with advanced and/or metastatic disease are poor. As such, the treatment of this patient population remains challenging. As a result, there is a clear unmet medical need, and designing and performing meaningful clinical studies are of utmost importance to improve the prognosis of this patient group. Therefore, the aim of this review is to briefly summarize state-of-the-art treatments for leiomyosarcoma patients and to describe trial characteristics needed for informative clinical studies.